2007
DOI: 10.1677/jme.1.02176
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 and Sp3 regulate glucokinase gene transcription in the liver of gilthead sea bream (Sparus aurata)

Abstract: To better understand the transcriptional machinery that governs glucokinase (GCK) expression, we have cloned and characterized the proximal promoter region of GCK from gilthead sea bream (Sparus aurata). The 5 0 -flanking region of GCK was isolated by chromosome walking. SMART RACE-PCR allowed us to locate the transcription start site 98 bp (bp) upstream from the translational start. Transfection analysis in HepG2 cells revealed the presence of a functional promoter in the 1397 bp 5 0 -flanking isolated fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
1
6
0
2
Order By: Relevance
“…For example, we found that while GK transcript levels were strongly down-regulated, G6Pase transcripts were upregulated in insulin-injected trout. Although in other fish (Egea et al, 2007) and mammals (Iynedjian, 2009) GK is always upregulated by insulin, in the present study its repression could be related to the counter-regulation during hypoglycaemia, blocking the large glucose entrance and phosphorylation. In the same sense, the increased G6Pase transcript level probably improves glucose export to the bloodstream, as observed in the mammalian liver under hypoglycaemic conditions (Bady et al, 2002).…”
Section: Acute Insulin Administration: Metabolic Regulation In Musclementioning
confidence: 47%
“…For example, we found that while GK transcript levels were strongly down-regulated, G6Pase transcripts were upregulated in insulin-injected trout. Although in other fish (Egea et al, 2007) and mammals (Iynedjian, 2009) GK is always upregulated by insulin, in the present study its repression could be related to the counter-regulation during hypoglycaemia, blocking the large glucose entrance and phosphorylation. In the same sense, the increased G6Pase transcript level probably improves glucose export to the bloodstream, as observed in the mammalian liver under hypoglycaemic conditions (Bady et al, 2002).…”
Section: Acute Insulin Administration: Metabolic Regulation In Musclementioning
confidence: 47%
“…15). Sp1 is a ubiquitous nuclear factor that mediates the effects of insulin in different cell types, regulating such processes as glucose metabolism, lipid biosynthesis (16)(17)(18). The abundance of nuclear Sp1 has been shown to be increased by insulin and can be posttranslationally regulated by phosphatidylinositol-3-OH kinase (PI-3K) and extracellular signal-regulated kinase (ERK)1/2 pathways in some cell models (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Los promotores "upstream" desencadenan la expresión de GK en tejidos no hepáticos, incluido el páncreas y el cerebro (Iynedjian, 2009). En peces, estudios realizados en dorada (Sparus aurata) revelan la presencia de un promotor de GK en el hígado (Egea et al, 2007).La expresión génica de GK en el conjunto del cerebro ha sido estudiada en dos especies de peces como son la trucha arco iris (Panserat et al, 2000) y el pez zebra (González-Álvarez et al, 2009). Además, la actividad/expresión génica de GK se ha descrito en cinco áreas específicas del cerebro tales como el telencéfalo, cerebro posterior, cerebro medio, hipotálamo (Soengas et al, 2006) e hipófisis (Polakof, comunicación personal).…”
unclassified
“…Los promotores "upstream" desencadenan la expresión de GK en tejidos no hepáticos, incluido el páncreas y el cerebro (Iynedjian, 2009). En peces, estudios realizados en dorada (Sparus aurata) revelan la presencia de un promotor de GK en el hígado (Egea et al, 2007).…”
unclassified